Age-related changes in the biochemical composition of the human aorta and their correlation with the delamination strength - Suchý, Tomáš; Horný, Lukáš; Šupová, Monika; Adámek, Tomáš; Blanková, Alžběta; Žaloudková, Margit; Grajciarová, Martina; Yakushko, Olena; Blassová, Tereza; Braun, Martin (Acta biomaterialia, 2024)
Various studies have correlated the mechanical properties of the aortic wall with its biochemical parameters and inner structure. Very few studies have addressed correlations with the cohesive properties, which are crucial for understanding fracture phenomena such as aortic dissection, i.e. a life-threatening process. Aimed at filling this gap, we conducted a comprehensive biochemical and histological analysis of human aortas (the ascending and descending thoracic and infrarenal abdominal aorta) from 34 cadavers obtained post-mortem during regular autopsies. The pentosidine, hydroxyproline and calcium contents, calcium/phosphorus molar ratio, degree of atherosclerosis, area fraction of elastin, collagen type I and III, alpha smooth muscle actin, vasa vasorum, vasa vasorum density, aortic wall thickness, thicknesses of the adventitia, media and intima were determined and correlated with the delamination forces in the longitudinal and circumferential directions of the vessel as determined from identical cadavers. The majority of the parameters determined did not indicate significant correlation with age, except for the calcium content and collagen maturation (enzymatic crosslinking). The main results concern differences between enzymatic and non-enzymatic crosslinking and those caused by the presence of atherosclerosis. The enzymatic crosslinking of collagen increased with age and was accompanied by a decrease in the delamination strength, while non-enzymatic crosslinking tended to decrease with age and was accompanied by an increase in the delamination strength. As the rate of calcification increased, the presence of atherosclerosis led to the formation of calcium phosphate plaques with higher solubility than the tissue without or with only mild signs of atherosclerosis. STATEMENT OF SIGNIFICANCE: This study presents a detailed biochemical and histological analysis of human aortic samples (ascending thoracic aorta, descending thoracic aorta and infrarenal abdominal aorta) taken from 34 cadavers. The contribution of this scientific study lies in the detailed biochemical comparison of the enzymatic and non-enzymatic glycosylation-derived crosslinks of vascular tissues and their influence on the delamination strength of the human aorta since, to the best of our knowledge, no such comprehensive studies exist in the literature. A further benefit concerns the notification of the limitations of the various analytical methods applied; an important factor that must be taken into account in such studies.
Keywords: Calcium; lysin; aorta; Delamination; Humans; lidé středního věku; Lysine; aktiny; vápník; Aged; Female; dospělí; Calcification; stárnutí; ateroskleróza; Vasa Vasorum; senioři; lidé; Collagen maturation; elastin; Aging; Arginine; FTIR; Human aorta; AGEs; Adult; ženské pohlaví; Male; Middle Aged; Elastin; Atherosclerosis; Hydroxyproline; arginin; Aged, 80 and over; Actins; senioři nad 80 let; mužské pohlaví; vasa vasorum; Aorta; hydroxyprolin